2023
DOI: 10.1111/1475-6765.12593
|View full text |Cite
|
Sign up to set email alerts
|

Those were the what? Contents of nostalgia, relative deprivation and radical right support

Abstract: Recent research suggests that emotions are a central motivation for radical right voting. One emotion that has gained particular interest is nostalgia: Radical right politicians use nostalgic rhetoric, and feeling nostalgic is associated with radical right support. However, while nostalgia is widely and frequently experienced, previous work differentiates personal contents of nostalgia (e.g., childhood) from group‐based contents (e.g., traditions) and suggests that only the latter is related to the radical rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…While unemployment does not seem to be a general predictor of nostalgia, there may be heterogeneity for specific party families, regions, or periods. Finally, surveys suggest that nostalgia may contribute to support for radical right parties (Lammers and Baldwin 2020;Versteegen 2023) and negative feelings towards immigrants (Smeekes et al 2021;Smeekes and Verkuyten 2015). Future studies could assess the connection between levels of immigration, support for radical right parties, and the prevalence and exact nature of nostalgic rhetoric.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While unemployment does not seem to be a general predictor of nostalgia, there may be heterogeneity for specific party families, regions, or periods. Finally, surveys suggest that nostalgia may contribute to support for radical right parties (Lammers and Baldwin 2020;Versteegen 2023) and negative feelings towards immigrants (Smeekes et al 2021;Smeekes and Verkuyten 2015). Future studies could assess the connection between levels of immigration, support for radical right parties, and the prevalence and exact nature of nostalgic rhetoric.…”
Section: Discussionmentioning
confidence: 99%
“…The populist narrative, particularly in combination with a right-wing ideology, goes with a vision often reconstructed from the past (Betz and Johnson 2004;Elçi 2022). Lammers and Baldwin (2020) show that a message of nostalgia related to a past 'characterized by political incorrectness' can be associated with increased support for populist radical right parties, a finding supported by Versteegen (2023), who uses Dutch panel data to show that nostalgic citizens tend to be less satisfied with the government and have a higher voting propensity for radical right parties.…”
Section: Nostalgia In Partisan Rhetoricmentioning
confidence: 92%
“…Likewise, interviewees pushed other Germans to adhere to the country's culture more strongly. Consistent with the common PRR narrative of a society in decline (Versteegen, 2023), several interviewees were concerned that German traditions would wane. Günther, for example, felt that 'German comes more or less from tradition and traditional values, which are now disappearing' , and Sabine wished to return to society 'just as it was back then.…”
Section: 12mentioning
confidence: 95%
“…As political support is always a function of demand and supply (Mols & Jetten, 2020), it is unsurprising that PRR parties actively picture a country in decline (e.g., Versteegen, 2023) that leaves majorities behind, disadvantaged, or no longer respected. Hence, these parties may drive majority members' experience of lacking uniqueness, rendering any relationship between an individual's perceived position in society and party support bidirectional.…”
Section: Optimal Distinctiveness and Prr Supportersmentioning
confidence: 99%
“…Empirical studies within this line of work have shown that feelings of national nostalgia -i.e., a longing for the good old days of the country -tend to result in exclusionary understandings of national identity based on ancestry and descent (i.e., ethnic nationhood) and negative attitudes toward (Muslim) immigrants (Smeekes, 2015;. Moreover, recent empirical work has demonstrated that the exclusionary responses that follow from national nostalgia can explain the link with PRRP support (Gest et al, 2018;Lammers and Baldwin, 2020;Schreurs, 2021;Versteegen, 2024). More specifically, it was found that national nostalgia among native Dutch majority members relates to more PPRP support because it translates into stronger support for their nativist ideology in the form of ethnic nationhood and anti-Muslim attitudes (Smeekes et al, 2021).…”
Section: Open Accessmentioning
confidence: 99%